PENGARUH PENEMPATAN PEGAWAI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KELAUTAN DAN PERIKANAN PROVINSI BANTEN - ., Syamsudin; Sulfiyah, Sifa (Sains Manajemen, 2015)
This study aims to determine the effect of staffing and working environment on the performance of employees at the Department of Marine and Fisheries Banten Province.The method used is descriptive and associative. The samples used were 75 of the 150 employees of the Department of Marine and Fisheries Banten Province. The sampling technique used is the technique of saturated samples. For analysis using correlation analysis and regression analysis with the help of SPSS 12.0 for Windows. Based on hypothesis testing, proved to staffing and working environment affect the performance of employees. Based on these results it can be concluded that the performance of employees will increase if staffing was appropriate and comfortable and conducive working environment.